Incisional hernia after liver transplantation: risk factors and health‐related quality of life. (12th June 2014) - de Goede, Barry; Eker, Hasan H.; Klitsie, Pieter J.; van Kempen, Bob J.H.; Polak, Wojtek G.; Hop, Wim C.J.; Metselaar, Herold J.; Tilanus, Hugo W.; Lange, Johan F.; Kazemier, Geert
Abstract The aim of this cross‐sectional study was to analyze the incidence of incisional hernia after liver transplantation (LT), to determine potential risk factors for their development, and to assess their impact on health‐related quality of life (HRQoL). Patients who underwent LT through a J‐shaped incision with a minimum follow‐up of three months were included. Follow‐up was conducted at the outpatient clinic. Short Form 36 (SF‐36) and body image questionnaire (BIQ) were used for the assessment of HRQoL. A total of 140 patients was evaluated. The mean follow‐up period was 33 (SD 20) months. Sixty patients (43%) were diagnosed with an incisional hernia. Multivariate analysis revealed surgical site infection (OR 5.27, p = 0.001), advanced age (OR 1.05, p = 0.003), and prolonged ICU stay (OR 1.54, p = 0.022) to be independent risk factors for development of incisional hernia after LT. Patients with an incisional hernia experienced significantly diminished HRQoL with respect to physical, social, and mental aspects. In conclusion, patients who undergo LT exhibit a high incidence of incisional hernia, which has a considerable impact on HRQoL. Development of incisional hernia was shown to be related to surgical site infection, advanced age, and prolonged ICU stay.